2005
DOI: 10.1002/hipo.20084
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal contributions to neurocognitive mapping in humans: A new model

Abstract: The ability of an organism to develop, maintain, and act upon an abstracted internal representation of spatially extensive environments can provide an increased chance in ensuring that organism's survival. Here, we propose a neurocognitive model of spatial representation describing how several different processes interact and segregate the differing types of information used to produce a unified cognitive map. This model proposes that view-based egocentric and vestibulomotor translational information are funct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 99 publications
(116 reference statements)
2
16
0
2
Order By: Relevance
“…Spatial strategies can be either egocentric (body-centred) or allocentric (environment-centred), and O' Keefe and Nadel (1978) have suggested that there is a dichotomy between the two (Roche et al, 2005). Learning the layout of an environment can involve strategies such as exploration and search, and in some cases the use of secondary information sources such as maps and photographs can aid the navigator in a novel or unfamiliar environment (Roche et al, 2005).…”
Section: Haptic Feedback For Pedestrian Navigationmentioning
confidence: 99%
See 3 more Smart Citations
“…Spatial strategies can be either egocentric (body-centred) or allocentric (environment-centred), and O' Keefe and Nadel (1978) have suggested that there is a dichotomy between the two (Roche et al, 2005). Learning the layout of an environment can involve strategies such as exploration and search, and in some cases the use of secondary information sources such as maps and photographs can aid the navigator in a novel or unfamiliar environment (Roche et al, 2005).…”
Section: Haptic Feedback For Pedestrian Navigationmentioning
confidence: 99%
“…Learning the layout of an environment can involve strategies such as exploration and search, and in some cases the use of secondary information sources such as maps and photographs can aid the navigator in a novel or unfamiliar environment (Roche et al, 2005). Two commonly used techniques to learn the layout of the environment are either gaining route-based knowledge or survey-based knowledge.…”
Section: Haptic Feedback For Pedestrian Navigationmentioning
confidence: 99%
See 2 more Smart Citations
“…Assessments of patients who have received ECT do not appear to consider the possibility of such impairments, despite their impact on everyday life. In our work on temporal lobe epilepsy (Mangaoang et al, 2004;Roche et al, 2005), we developed a number of tasks (the Landmark Location, Landmark Recognition and Virtual Map tasks) to measure the ability of patients with left or right unilateral hippocampal damage to recognise photographs of well-known Dublin landmarks and to accurately name their location on a modified map of the city. Patients also described in writing the routes they would take to get from one landmark to another on a map of a virtual city.…”
Section: Topographical Memorymentioning
confidence: 99%